In situ epoxide generation by dimethyldioxirane oxidation and the use of epichlorohydrin in the flow synthesis of a library of β-amino alcohols - Cossar, Peter J. (R Soc Open Sci, 2018)
The flow coupling of epichlorohydrin with substituted phenols, while efficient, limits the nature of the epoxide available for the development of focused libraries of β-amino alcohols. This limitation was encountered in the production of analogues of 1-(4-nitrophenoxy)-3-((2-((4-(trifluoromethyl)pyrimidin-2-yl)amino)ethyl)amino)propan-2-ol 1, a potential antibiotic lead. The in situ (flow) generation of dimethyldoxirane (DMDO) and subsequent flow olefin epoxidation abrogates this limitation and afforded facile access to structurally diverse β-amino alcohols. Analogues of 1 were readily accessed either via (i) a flow/microwave hybrid approach, or (ii) a sequential flow approach. Key steps were the in situ generation of DMDO, with olefin epoxidation in typically good yields and a flow-mediated ring opening aminolysis to form an expanded library of β-amino alcohols 1 and 10a–18g, resulting in modest (11a, 21%) to excellent (12g, 80%) yields. Alternatively flow coupling of epichlorohydrin with phenols 4a–4m (22%–89%) and a Bi(OTf)(3) catalysed microwave ring opening with amines afforded a select range of β-amino alcohols, but with lower levels of aminolysis regiocontrol than the sequential flow approach.